Spirituality, a Neglected Dimension in Improving the Lifestyle of Coronary Artery Patients by Nurses: A Scoping Review - Fahimeh Abedini; Jamileh Mokhtari Nouri; Seyed Tayeb Moradian (Wolters Kluwer Medknow Publications, 2024)
Background: By modifying the lifestyle of patients, the risk factors of Coronary Artery Diseases (CADs) are adjusted. This study was performed with the aim to investigate the role of nurses in the lifestyle of coronary artery patients. Materials and Methods: This scoping review was conducted with the question of the role of nurses in improving the lifestyle of coronary artery patients. This study was conducted in databases and search engines of ScienceDirect, Springer, Scopus, PubMed, MEDLINE, and Google Scholar for English texts, and in the Magiran and Scientific Information Database (SID) databases and search engines for the texts printed in Persian. The search for articles printed from 2012 to 2022 was conducted based on the keywords used in the title and abstract of the articles. The keywords used to search domestic databases included nursing, lifestyle and healthy lifestyle, and heart diseases (based on MeSH). Results: Nurses have made significant efforts and performed interventions to improve the lifestyle of coronary artery patients through guidance and education regarding the improvement of their diet and mobility, compliance with their treatment regimen, and reduction of the risk factors of CAD. In the psychological dimension, they had a positive effect in some fields such as stress management and mental health. However, in the spiritual dimension, effective studies and interventions have not been conducted by nurses. Conclusions: The role of nurses in the lifestyle of coronary artery patients is effective in the physical dimension, limited in the psychological dimension, and neglected in the spiritual dimension.